Symbolic Language in the Stories of Bible and Quran: A Comparative Study Between Song of the Songs and Chapter of Ants - Abdul Rahman Hussein Obeid; Adnan Moh'D Abdullah Shalash (Institute of Research and Journals (IRAJ), 2024)
Non-Indexed Publication